(3GdMLI aj TQbGJ GHf MLIs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s; (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3adeG fRd HeUQ eG fRd ef GdeUGH ef ONhd GHf MLI GdeTFhe EdjgG hEPG gh bO HOd fYeI Gddg JYGdi HGdcaQGf hNGf eYGedJg hGddg dG jMH cd NhGf, Ef PcQ GdeJbOehf GSJWGd HdSGfg s
(3BNQgG (B:s
(3hgPG OjhGf TYQj Hjf CXgQ GdfGS adjJUaMg ef TGA eY Cfg CcHQ MLekG ef OjhGf GHf MLI hbO CTQJ Edi gPG GdeYfi aj JCFjJj GdeTGQ EdjgG eRedG HTYGQ GdJhQjI s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B254 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B631s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs